Supramolecular interaction facilitated small molecule films for organic field effect transistors - Arulkashmir, Arulraj; Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Jangid, Manoj K.; Krishnamoorthy, Kothandam (Polymer Chemistry, 2012)
Metalloporphyrins and metal free porphyrins have been explored as active materials in field effect transistors. Amorphous forms of these porphyrins are preferred over their crystalline analogue due to the ease of solution processability. To achieve solution processability, a metalloporphyrin was anchored on a vinyl polymer by taking advantage of the supramolecular interaction between the metal and the pyridine moiety of the polymer. Non covalent bonding was preferred because it provides an opportunity to better manipulate the polymer's properties compared to its covalent bonding analogue. The binding between the porphyrin and the polymer was optimised in solution and the supramolecular complex was spun on various substrates to form thin films. The porphyrin was found to be uniformly distributed throughout the polymer films contrary to the existing approaches, wherein small molecule phase segregates in the polymer film. Field effect transistors were fabricated using the porphyrin-polymer complex and the device parameters were measured at atmospheric condition. The devices annealed at 80 degrees C showed hole carrier mobility of 2.0 x 10(-4) cm(2) V-1 s(-1) with charge trapping at the dielectric semiconductor interface. Furthermore, the high carrier mobility observed at low temperature annealing makes this supramolecular complex an attractive candidate to explore in flexible substrates.